OPERE ERKEN EVRE AKCİĞER KANSERİ HASTALARINDA PROGNOSTİK_x000D_ FAKTÖRLER RETROSPEKTİF TEK MERKEZ SONUÇLARI - (:unkn) unknown (My University, 2020)
Amaç: Küçük hücreli dışı akciğer kanseri (KHDAK) tüm akciğer kanserlerinin %85’ini oluşturmaktadır. Erken evre hastalıkta cerrahi ile küratif tedavi hedeflense de nüks sık görülmektedir. Bu çalışmada merkezimizde opere olan erken evre KHDAK tanılı hastaların sonuçlarını ve prognoza etkili faktörleri retrospektif olarak değerlendirdik.Materyal ve Metot: 2006-2018 yılları arasında kliniğimize başvuran 166 opere erken evre KHDAK hastasının dosyası retrospektif olarak değerlendirildi. Bulgular SPSS kullanılarak analiz edildi. Histopatolojik ve klinik özelliklerin için prognostik önemi araştırıldı.Bulgular: Hastalarımızın %84’ü erkekti. Medyan tanı yaşı 61 (39-82)’di. En sık görülen patolojik alt tip adenokarsinomdu. Medyan hastalıksız sağkalım (HSK) ve genel sağkalım (GSK) 76 ay (%95CI:32.1-110.0) ve 87 aydı (95%CI:59.8-114.1). Çok değişkenli analizde vaskuler invazyon varlığı daha kötü HSK ve GSK için bağımsız prognostik faktördü (HR: 2,5 ve 2.3). Adenokarsinom solid patern isesadece daha kötü HSK ile ilişkiliydi (HR:1.7)..Sonuç: Çalışmamızda vaskuler invazyon varlığının ve solid tip adenokarsinomun kötü sağ kalım ile ilişkili olduğunu gösterdik.

Aim: Non-small cell lung cancer (NSCLC) accounts for 85% of all lung cancers. Although curative treatment is surgery in the early stages, disease relapse is common. In this study, we retrospectively evaluated the prognostic factors and outcomes of operated NSCLC cases._x000D_ _x000D_ Materials and Methods: Retrospective analysis of data from 166 patients with early stage NSCLC who presented after surgery and treated and followed in our clinic between 2006-2018 was performed. Histopathologic features and clinical findings were investigated as prognostic factors.The findings were analyzed using SPSS._x000D_ _x000D_ Results: At the time of diagnosis, median age was 61 (39-82) and 84% of the patients were male. Most common pathologic subtype was adenocarcinoma. Median disease free survival (DFS) and overall survival (OS) were 76 months (%95CI:32.1-110.0) and 87 months (95%CI:59.8-114.1). ). In multivariate analysis, presence of vascular invasion was found to be independent prognostic factors for both DFS and OS (HR:2.5 and 2.3, respectively). Adenocarcinoma solid pattern was only associated with worse disease-free survival (HR: 1.7)._x000D_ _x000D_ Conclusion: In our study, we showed that the presence of vascular invasion and solid-type adenocarcinoma is associated with poor survival._x000D_
Prognostic Factors in Operated Early Stage Lung Cancer Patients- Retrospective Single Center Data